Political Realities as Portrayed in `KuusaaGadoo - Alemitu Oli; Eriste Akawak (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to demonstrate how GadisaBiru who wrote the novel `KuusaaGadoo` represents the Oromo`s political issues in a realistic way in the life of characters and the major themes of the novel. The study is qualitative research, it involves textual analysis method together with relevant conceptual tools and frameworks and therefore it is analytical. Furthermore, the data used for the research is taken from primary source which is `Kuusaa Gadoo`. From the novel different extracts are taken based on research questions. Extracts used as a data were classified under each topic and analyzed using textual analysis methods and realism theory. Then, the analysis and discussion were undertaken by using the concept of scholars to make the research more visible and logical. As a philosophy of realism theory, realism portrays the world as it really appears. Therefore, to evaluate the realistic representations of different agenda of the research, it is crucial to bring the idea in the text to the actual world. From the analysis and discussion made it is found that, in `KuusaaGadoo`, all events and episodes were realized in the novel without any fantasy and extraordinary overstatement. The political situation of the Derg regime as reflected in `KusaaGadoo` was not participatory. Political power was dominated by specific ethnic group and the Oromos were under domination. To disuniting Oromos and making to hatred their own identity and appreciate Amharization segregation, renaming and despicableness were used and the name of Oromo people and Oromo`s land changed to Amharic. In general, the novel `KuusaaGadoo` reflects the real life situation of Oromo peoples during the Derg regime, the author critically observed the real picture of the society`s life and portrayed logically. The main theme of the story is day to day injustice accumulated in human mind invites revenge which is the extreme level of decision in life.